The Effectiveness of E-Book Based Learning Media in Physics Education During the Covid-19 Pandemic - Neza Almaida; Rifqi Arya Permanagraha; Wiwin Novianti (Yayasan Darussalam Bengkulu, 2023)
The Covid-19 pandemic has transformed higher education by accelerating the adoption of digital learning resources, with e-books emerging as one of the primary media to support online learning. However, despite their accessibility and flexibility, questions remain about their actual effectiveness in facilitating student learning, particularly in physics education where abstract concepts require diverse instructional strategies. This study employed a quantitative descriptive design using a structured questionnaire distributed via Google Forms to 28 undergraduate students in the Physics Education program at Universitas Indraprasta PGRI, Jakarta. The instrument consisted of multiple-choice and Likert-scale items to capture patterns of e-book use, perceived effectiveness, and student satisfaction. The findings showed that 92.9% of respondents acknowledged e-books as beneficial for their learning, and 85.7% reported that they improved their understanding of physics content. Nevertheless, only 28.6% frequently used e-books, and the average satisfaction score was moderate at 3.39, indicating that while students recognize the instructional value of e-books, their actual adoption remains limited due to factors such as monotonous presentation and lack of interactivity. These results are consistent with prior studies on digital reading preferences, but the study contributes novel insights by highlighting the paradox between high perceived usefulness and low frequency of e-book use in the context of physics education during pandemic-driven online learning. The implication of this research is that e-books should be redesigned with multimedia features, interactive problem-solving tasks, and integration into blended instructional approaches to enhance their pedagogical impact and ensure sustained student engagement in post-pandemic learning environments.